2019
DOI: 10.1021/acsami.8b21393
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Nanoscale Topographies for Osteogenic Differentiation of Mesenchymal Stem Cells

Abstract: Nanotopography with length scales of the order of extracellular matrix elements offers the possibility of regulating cell behavior. Investigation of the impact of nanotopography on cell response has been limited by inability to precisely control geometries, especially at high spatial resolutions, and across practically large areas. In this paper, we demonstrate well-controlled and periodic nanopillar arrays of silicon and investigate their impact on osteogenic differentiation of human mesenchymal stem cells (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…Another study suggested that nanopillar arrays (silicon nanopillar arrays with critical dimensions in the range of 40-200 nm) can enhance osteogenic differentiation of human mesenchymal stem cells. 14 Although different nanostructure surfaces are used, the specific cell responses to nanoscale topography are confirmed in the present study. Moreover, the present study offers a new nanopit structure with directional osteo-differentiation effect of hADSCs.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Another study suggested that nanopillar arrays (silicon nanopillar arrays with critical dimensions in the range of 40-200 nm) can enhance osteogenic differentiation of human mesenchymal stem cells. 14 Although different nanostructure surfaces are used, the specific cell responses to nanoscale topography are confirmed in the present study. Moreover, the present study offers a new nanopit structure with directional osteo-differentiation effect of hADSCs.…”
Section: Discussionsupporting
confidence: 59%
“…Recently, the nanoscale surface topography was proven to have highly promising effects on regulating survival, proliferation, migration, and differentiation of adult MSCs. 13,14 Implant materials with nanostructured surfaces have shown promising applications in orthopedic surgical field. 15 The nanoscale surface morphology remarkably determines cellular responses, which have an important role in the optimization of medical implant biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…In biomedicine, surface topography is also able to direct cellular behaviors, including cell migration, adhesion, proliferation, and differentiation. The latest studies reveal that nanoscale topography can direct mesenchymal stem cells (MSCs) to differentiate into osteoblasts so as to reinforce early osseointegration [9][10][11][12]. It is even reported that combined micro-and nano-scale surface modification can cause MSCs to differentiate into contractile smooth muscle cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…A representative AFM image recorded in the tapping mode is shown in Figure 3b. The characterization is critical for each batch of samples, and it is possible to scale the process to several batches of wafers [41]. Points A, B, C, and D correspond to four positions representing systematically increasing radial distances from the center to the edge of the wafer.…”
Section: Reproducibility and Scalabilitymentioning
confidence: 99%